Implementasi LKS Dengan Pendekatan STEM (Science, Technology, Engineering, And Mathematics) Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Diyah Ayu Budi Lestari; Budi Astuti; Teguh Darsono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
The purpose of this study is to overcome the increased of critical thinkingÃ¢â¬â¢ students after they used worksheet with STEM approach. This research method is experiment method that consist of preparing, implementation, and data processing. Increasing of critical thinking can be measured by pretest-posttest problems. The result of data normalization show that data have normal distributed so next test is n-gain test. Result of the n-gain test pretest-posttest scores around 0.5 (medium level categorized). The highest improvement is 0.9 at evaluation aspect and lowest increase is 0.3 at interpretation aspect.